228k views
4 votes
Square root3(square root3+2square root12) simplify it.Answer should be square root 3.

Square root3(square root3+2square root12) simplify it.Answer should be square root-example-1

2 Answers

7 votes

Answer:

D

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Given


√(3) (
√(3) + 2
√(12) ) ← distribute

= 3 + 2
√(36)

= 3 + (2 × 6)

= 3 + 12

= 15 → D

User Hans Brende
by
5.3k points
4 votes

Answer:

sqrt3[sqrt3+2sqrt12]=sqrt3[sqrt3+4sqrt3] = sqrt3[5sqrt3= 3x5 =15

User GarethOwen
by
5.2k points